2010
DOI: 10.1186/1744-8603-6-3
|View full text |Cite
|
Sign up to set email alerts
|

National and subnational HIV/AIDS coordination: are global health initiatives closing the gap between intent and practice?

Abstract: BackgroundA coordinated response to HIV/AIDS remains one of the 'grand challenges' facing policymakers today. Global health initiatives (GHIs) have the potential both to facilitate and exacerbate coordination at the national and subnational level. Evidence of the effects of GHIs on coordination is beginning to emerge but has hitherto been limited to single-country studies and broad-brush reviews. To date, no study has provided a focused synthesis of the effects of GHIs on national and subnational health system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 20 publications
1
93
0
9
Order By: Relevance
“…For instance, the Global Fund CCM has brought together representatives of national governments, civil society, the private sector, and multilateral and bilateral donor institutions to help coordinate the development of national proposals, and to help better coordinate Global Fund grants with other national health and broader development programs (Global Fund 2012). Initial evidence shows that the country-level programs have improved coordination and transparency, but that they have not yet succeeded in comprehensively coordinating the efforts of all donors (Spicer et al 2010). Moreover, in 13 some cases the different coordinating initiatives have themselves contributed to coordination problems.…”
Section: Effectiveness and Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the Global Fund CCM has brought together representatives of national governments, civil society, the private sector, and multilateral and bilateral donor institutions to help coordinate the development of national proposals, and to help better coordinate Global Fund grants with other national health and broader development programs (Global Fund 2012). Initial evidence shows that the country-level programs have improved coordination and transparency, but that they have not yet succeeded in comprehensively coordinating the efforts of all donors (Spicer et al 2010). Moreover, in 13 some cases the different coordinating initiatives have themselves contributed to coordination problems.…”
Section: Effectiveness and Efficiencymentioning
confidence: 99%
“…• Partnerships and coordinating mechanisms could improve participation, transparency, and efficiency (Spicer et al 2010); • Frequent, routine publication by all donor institutions of all their committed and disbursed contributions to global health would increase transparency, accountability, and coordination; • Mutual performance assessment and evaluations among different organizations could increase accountability; • A strengthening of a central organization, such as WHO or a global health monitoring institute, could improve effectiveness and efficiency (Sridhar 2009); and • A global health constitution outlining the duties and obligations of actors in global health could improve transparency and effectiveness (Ruger 2012). …”
Section: The Way Forwardmentioning
confidence: 99%
“…A seven-country study by Spicer et al (2010) found that although GHIs (the Global Fund for AIDS, Tuberculosis and Malaria particularly) have had positive effects on co-ordination at the national level, they increased the complexity of the aid architecture, undermined alignment and lacked harmonization, especially at the sub-national level (Spicer et al 2010). In contrast, Dodd and Lane (2010) found that global health partnerships have successfully innovated new approaches to raising and delivering funds and can provide longer-term funding, from which other donors should learn-more details on these can be found in Box 2.…”
Section: Box 2: Global Health Initiativesmentioning
confidence: 99%
“…The second study, Spicer et al (2010), examined the effects of three GHIs-the Global Fund to fight AIDS, Tuberculosis and Malaria (GFATM), the President's Emergency Plan for AIDS Relief (PEPFAR) and the World Bank's Multi-country AIDS Programme (MAP)-on co-ordination in seven countries in Europe, Asia, Africa and South America. The study involved 379 in-depth interviews with stakeholders at the national and sub-national level.…”
Section: Box 2: Global Health Initiativesmentioning
confidence: 99%
“…2 Although DAH has contributed to many important achievements (eg, eradication of small pox, treatment for patients living with HIV/AIDS) some of this spending may have inadvertently weakened the local health systems that it intended to help. [3][4][5][6] Action through global health partnerships (GHPs) is a contrasting strategy to traditional DAH for accelerating progress toward global health targets. See Table 1 for a comparison of traditional DAH and GHPs.…”
Section: Global Health Partnershipsmentioning
confidence: 99%